Qualitative Tussles in Undertaking a Grounded Theory Study - Judith A. Holton (Grounded Theory Review: An International Journal, 2009)
Those who’ve been trained to regard grounded theory as a qualitative research method frequently struggle to ‘unlearn’ qualitative data analysis dicta when undertaking a classic grounded theory study. A plethora of research methods texts that support this notion of grounded theory as a qualitative method are primarily responsible for the ensuing confusion. Further supporting this popular misconception are many papers published in leading academic journals and all too often the pressuring advice of thesis supervisors. This paper addresses specifically two issues that can create frustrating tussles for novice grounded theorists, especially in challenging such ‘authoritative’ perspectives: avoiding preconception and transcending descriptive detail. In addressing these persistent tussles, the reader is reminded of the fundamental distinction of grounded theory as a methodology for the emergent discovery of conceptually abstract theory from empirical data.